Method for producing filler-containing composition by means of specific curing scheme
The composite material containing filler is cured by high-frequency heating method, which solves the problems of high temperature, high pressure and long-term curing in the prior art, and achieves the effects of rapid curing, low pressure and high density, and improves cost-effectiveness.
Patent Information
- Application Number
- CN202380052579.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-05-25
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art requires high temperature, high pressure and extended curing time to obtain ideal high density and stability, resulting in higher costs when manufacturing filler-containing composite materials containing specific polyesters.
The compositions containing fillers and specific polyesters in the range of 0.1 to 0.8 are cured by high frequency heating (HF heating) method, reducing curing time and reducing pressure requirements.
The curing process is achieved in a short time, reducing the curing pressure, while maintaining high density and good shape stability, and improving the cost-effectiveness of manufacturing filler-containing composite materials.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a composition comprising a filler and a specific polyester, especially a bio-based polyester. Background Art
[0002] WO 2012 / 140237 describes the manufacture of a composite material comprising 10-98 wt.% of a bio-based particulate or fibrous filler and at least 2 wt.% of a bio-based polyester, wherein the method comprises combining the filler and the polyester (or a precursor thereof) and subjecting the combination to a temperature of 120°C and at least 1×10 6 The pressure curing step is carried out at a pressure of 10 bar (10 bar). The polyester is the reaction product of an aliphatic polyol having 2 to 15 carbon atoms, preferably glycerol, and an aliphatic polyacid having 3 to 15 carbon atoms, especially a triacid such as citric acid.
[0003] WO 2012 / 140239 describes the production of composite materials containing synthetic fillers (eg glass fiber fillers) using the same polyester as used in 2012 / 140237. In the examples, for example, curing is performed for 12 hours.
[0004] In seeking to commercially develop filled composites using specified polyesters, it has been found that in order to obtain materials having the desired high density and the degree of polymerization required to obtain products having good stability, high temperatures, high pressures and extended curing times are required. Extended curing at relatively high temperatures and pressures is associated with relatively high costs.
[0005] There is a need in the art for a method of making a composition based on a defined polyester that can solve these problems. The present invention provides such a method of making. Summary of the invention
[0006] Therefore, the present invention relates to a method for producing a composite object containing filler, comprising the following steps:
[0007] - providing a composition comprising a filler and a polymer, wherein the polymer is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms, the degree of polymerization of the polyester being in the range of 0.1 to 0.8, the degree of polymerization being the ratio between the fraction of functional groups that have reacted and the maximum number of functional groups that can react, and
[0008] - subjecting the composition to a curing step, wherein the composition is cured at a temperature of at most 1×10 6 High frequency heating is performed at a pressure of 100 Pa (10 bar) for a period of 10 seconds to 30 minutes, resulting in the formation of a composite object.
[0009] Surprisingly, it was found that the combination used herein using a specific curing scheme and a manufacturing method of a specific polymer produced particularly attractive results. Specifically, a rapid heating rate was observed, which allowed the curing time to be reduced. In addition, a uniform heating distribution was obtained, which surprisingly also resulted in relatively thick objects. Finally, it was particularly surprising to find that the curing pressure could be reduced while still obtaining an attractive object of high density and good shape stability. This makes it possible to manufacture a composite material containing fillers in a cost-effective manner.
[0010] Without wishing to be bound by theory, it is believed that the advantageous effects of the present invention may be partly related to the nature of the monomers, especially when monomers having a relatively low number of carbon atoms compared to the number of oxygen-containing reactive groups are used. For example, this applies when the aliphatic polyol comprises a large amount of polyols having at least 3 hydroxyl groups and the aliphatic polycarboxylic acid comprises a large amount of tricarboxylic acids.
[0011] The present invention will be discussed in more detail below.
[0012] In the method of the present invention, a curing step is performed in which a composition comprising a filler and a specific polyester having a degree of polymerization ranging from 0.1 to 0.8 is subjected to high frequency heating for a period of 10 seconds to 30 minutes.
[0013] In the context of the present invention, high frequency heating (also referred to herein as HF heating) is exposing an object to an alternating electromagnetic field with a frequency in the range of 3 to 100 MHz, in particular 10 to 50 MHz. Frequencies used for industrial purposes are 13.56 MHz, 27.12 MHz and 40.68 MHz, with 27.12 MHz being particularly used.
[0014] The energy supplied to the curing step depends on the field strength of the electromagnetic field. The required energy input depends on the size of the object to be cured and the nature of the equipment. Values in the range of 1000 to 20.000 V can be used as a general guideline, but this value is within the range of a person skilled in the art to select a suitable voltage.
[0015] Depending on the size and shape of the object to be cured and the power provided, the HF heating step may be carried out for a period of 10 seconds to 30 minutes. A period of less than 10 seconds is usually insufficient to reach the desired temperature at the core of the object. A period of more than 30 minutes is usually not required. The heating is preferably carried out for a period of 10 seconds to 20 minutes, especially 20 seconds to 10 minutes, more especially 20 seconds to 5 minutes or even 20 seconds to 3 minutes.
[0016] Curing can be performed in a single step or in multiple steps. In one embodiment, two curing steps are performed. If necessary, the object to be cured can be processed between the two curing steps, wherein the processing may include any steps that change the shape or surface properties of the object. However, in general, a single curing step is sufficient.
[0017] Suitable equipment for HF heating is commercially available.
[0018] The curing step can be up to 1×10 6 Pa (10 bar). However, in general, such high pressure is not required. The pressure can be up to 8×10 5 Pa (8 bar), especially up to 6×10 5 Pa (6 bar) or up to 4×10 5 Pa (4 bar), in some embodiments up to 3×10 5 Pa (3 bar). The lowest level can be 1.1×10 5 Pa (1.1 bar), especially 1.5×10 5 Pa (1.5 bar).
[0019] It may be more attractive to perform the curing step in two or more steps, wherein the pressure of the first curing step is lower than the pressure of the second curing step. In this case, the first curing step may be primarily a heating step, resulting in a softening of the polymer. A softer polymer may exhibit better flow properties under pressure. This allows the polymer to redistribute under pressure during the heating step, producing a composite material with better properties.
[0020] It may be more attractive for parts of the HF heating apparatus that come into contact with the composition to be cured to be either heatable or thermally insulated to prevent heat generated by the RF heating from escaping to the environment.
[0021] polymer
[0022] The polymer used in the present invention is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms, and the degree of polymerization of the polyester is in the range of 0.1 to 0.8, the degree of polymerization referring to the ratio between the portion of the functional groups that have reacted and the maximum number of the functional groups that can react.
[0023] Polyol monomers suitable for use in the present invention include aliphatic polyols having 2 to 15 carbon atoms. The aliphatic polyol does not include any aromatic moieties, nitrogen atoms or sulfur atoms. In certain embodiments, the aliphatic polyol is composed of carbon, oxygen and hydrogen atoms. The aliphatic polyol contains at least two hydroxyl groups, preferably at least three hydroxyl groups. In general, the number of hydroxyl groups is 10 or less, preferably 8 or less, more preferably 6 or less. The aliphatic polyol has 2 to 15 carbon atoms, preferably 3 to 10 carbon atoms. Examples of suitable aliphatic polyols are 1,2-propylene glycol, 1,3-propylene glycol, 1,2-ethylene glycol, 1,4-butylene glycol, glycerol, sorbitol, xylitol and mannitol. Glycerol, sorbitol, xylitol and mannitol are preferred examples of suitable aliphatic polyols. Glycerol is the most preferred example of suitable aliphatic polyols. One reason is that glycerol has a melting point of 20°C, which is easy to process (compared to, for example, xylitol, sorbitol, and mannitol, which all have melting points above 90°C). In addition, glycerol is readily available and produces polymers with favorable properties. Therefore, in some embodiments, the aliphatic polyol consists essentially of glycerol. As used herein, "consisting essentially of" means that other components (herein, other aliphatic polyols) may be present in an amount that does not adversely affect the properties of the material.
[0024] The aliphatic polyol may contain at least 30 wt.% of a polyol having at least 3 hydroxyl groups, in particular at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.%. In some embodiments, the aliphatic polyol consists essentially of a polyol having at least 3 hydroxyl groups.
[0025] Mixtures of different aliphatic polyols can also be used. The aliphatic polyol may contain at least 50 mol% of glycerol, sorbitol, xylitol or mannitol, preferably at least 70 mol%, preferably at least 90 mol%. Preferably, the remainder is an aliphatic polyol having 3 to 10 carbon atoms. The polyol preferably contains at least 70 mol% of glycerol, preferably at least 90 mol%, more preferably at least 95 mol%.
[0026] In some embodiments, the ratio of hydroxyl groups to the number of carbon atoms in the aliphatic polyol is from 1:4 (i.e., one hydroxyl group for every four carbon atoms) to 1:1 (i.e., one hydroxyl group for each carbon atom). The ratio of hydroxyl groups to the number of carbon atoms is preferably from 1:3 to 1:1, more preferably from 1:2 to 1:1, and even more preferably from 1:1.5 to 1:1. Compounds having a 1:1 ratio of hydroxyl groups to carbon atoms are considered to be particularly preferred.
[0027] Polycarboxylic acid monomers suitable for use in the present invention include aliphatic polycarboxylic acids having 3 to 15 carbon atoms, preferably 3 to 10 carbon atoms, and in certain embodiments, 3 to 6 carbon atoms. The aliphatic polycarboxylic acid does not include an aromatic moiety or any nitrogen or sulfur atom. In certain embodiments, the aliphatic polycarboxylic acid is composed of carbon, oxygen and hydrogen atoms. The aliphatic polycarboxylic acid comprises at least two carboxylic acid groups, preferably three carboxylic acid groups. In general, the number of carboxylic acid groups is 10 or less, preferably 8 or less, more preferably 6 or less.
[0028] In one embodiment, the aliphatic polycarboxylic acid comprises at least 10 wt.% tricarboxylic acid based on the total amount of the aliphatic polycarboxylic acid. Based on the total amount of acid, the aliphatic polycarboxylic acid may comprise at least 30 wt.%, preferably at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.% tricarboxylic acid. In some embodiments, the aliphatic polycarboxylic acid consists essentially of tricarboxylic acid, preferably consists essentially of citric acid.
[0029] The aliphatic polycarboxylic acid can be a mixture of acids, such as a mixture of tricarboxylic acids and dicarboxylic acids. In some embodiments, based on the total amount of the aliphatic polycarboxylic acid, the aliphatic polycarboxylic acid comprises at least 2 wt.%, preferably at least 5 wt.%, more preferably at least 10 wt.% of dicarboxylic acids and at least 10 wt.%, preferably at least 30 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably at least 95 wt.% of the combination of tricarboxylic acids.
[0030] If used, the dicarboxylic acid can be any dicarboxylic acid having two carboxylic acid groups and generally up to 15 carbon atoms. Examples of suitable dicarboxylic acids include itaconic acid, malic acid, succinic acid, glutaric acid, adipic acid, succinic acid, oxalic acid, maleic acid, fumaric acid, muconic acid, suberic acid and azelaic acid. Itaconic acid and succinic acid can be preferred. In one embodiment, tricarboxylic acids are used. If used, the tricarboxylic acid can be any tricarboxylic acid having three carboxylic acid groups and generally up to 15 carbon atoms. Examples include citric acid, isocitric acid, aconitic acid (cis and trans) and 3-carboxy-cis, cis-muconic acid. For reasons of cost and availability, it is considered preferred to use citric acid. Where applicable, the acid can also be provided in the form of anhydrides, such as citric anhydride.
[0031] In one embodiment, the polymer is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms, wherein the aliphatic polyol comprises at least 30 wt.%, especially at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.% of a polyol having at least 3 hydroxyl groups, the aliphatic polyol having at least 3 hydroxyl groups being preferably glycerol, and the aliphatic polycarboxylic acid comprises at least 30 wt.%, preferably at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.% of a tricarboxylic acid, based on the total amount of acid, the tricarboxylic acid being preferably citric acid.
[0032] In one embodiment of the present invention, the polymer is derived from a combination of polyol monomers and polycarboxylic acid monomers, wherein
[0033] The polyol monomer is preferably selected from aliphatic polyols having 2 to 15 carbon atoms and having at least three hydroxyl groups, such as glycerol, sorbitol, xylitol and mannitol, especially glycerol,
[0034] The polycarboxylic acid monomer is selected from aliphatic polycarboxylic acids having 3 to 15 carbon atoms and having at least three carboxylic acid groups, such as citric acid, isocitric acid, aconitic acid (cis and trans) and 3-carboxy-cis,cis-muconic acid, especially citric acid.
[0035] The polymer with a degree of polymerization in the range of 0.1 to 0.8 is obtained by the polymerization of a combination of polyol monomers and polycarboxylic acid monomers. The polymerization can be carried out by combining the monomers to form a liquid phase. Depending on the nature of the compound, the polymerization can be achieved, for example, by heating the mixture of the components to a temperature at which the acid is dissolved in the alcohol, especially in glycerol. Depending on the nature of the compound, this temperature can be, for example, a temperature in the range of 20°C to 250°C, such as 40°C to 200°C, such as 60°C to 200°C or 90°C to 200°C. In one embodiment, the mixture can be heated and mixed at a temperature of 80°C to 200°C, especially 100°C to 200°C, in certain embodiments at a temperature of 120°C to 180°C for 1 minute to 2 hours, more especially 5 minutes to 45 minutes. If necessary, a suitable solvent, such as water, can be present. Preferably, the amount of water will remain limited because water evaporation consumes energy. It is preferred to add up to 30wt.% of water, especially up to 20wt.% of water.
[0036] Alternatively, a suitable catalyst may be used to prepare the polyester. Catalysts suitable for making polyesters are known in the art. Preferred catalysts are those that do not contain heavy metals. Suitable catalysts are strong acids such as, but not limited to, hydrochloric acid, hydroiodic acid and hydrobromic acid, sulfuric acid (H2SO4), nitric acid (HNO3), chloric acid (HClO3), boric acid, sodium hypophosphite, perchloric acid (HClO4), trifluoroacetic acid, p-toluenesulfonic acid, sulfonic acid and trifluoromethanesulfonic acid. Catalysts such as tetrabutyl titanate (Ti-butoxide), stannous octanoate (Sn-octanoate), zinc acetate and manganese acetate may also be used, although these catalysts may be less preferred.
[0037] The degree of polymerization of the polymer used as starting material in the present invention is between 0.1 and 0.8. In the context of this specification, the degree of polymerization refers to the ratio between the fraction of functional groups that have reacted and the maximum number of functional groups that can react. The degree of polymerization can be determined by the acid number (especially values below 0.5) or by gravimetric analysis (especially values above 0.5).
[0038] Obviously, in order to determine the degree of polymerization of a polymer derived from an aliphatic polyol and an aliphatic polycarboxylic acid with an unknown degree of polymerization using gravimetric analysis, a sample of the polymer with an unknown degree of polymerization is cured at a temperature of 100° C. to 220° C. until no more water is lost. The degree of polymerization of the polymer is then 1, making it possible to use the water lost during curing to back-calculate the degree of polymerization of the sample polymer.
[0039] As will be apparent to those skilled in the art, the determination of the degree of polymerization by acid value titration, for example with KOH, can be performed in the following manner. A certain amount of polymer is dissolved in a solvent and then titrated, for example with KOH, to determine the acid value. By comparing the measured acid value with the theoretical acid value of the dissolved amount of polymer, the conversion can be calculated. Depending on the available information, the degree of polymerization can also be determined by comparing the acid value of the reaction mixture with the theoretical acid value of the total monomers.
[0040] As is obvious to the person skilled in the art, the degree of polymerization can also be determined by means of the ester value (EV). This method is applicable to both liquid and non-liquid samples. Here, for example, a certain amount of polymer is hydrolyzed with KOH. By back titration, the absorption of KOH can be measured to obtain the ester value. By comparing the measured ester value with the theoretical ester value of this amount of polymer, the conversion can be calculated.
[0041] The ideal degree of polymerization of the composition provided to the curing step will depend on a variety of factors. Specifically, at this stage of the process, the advantage of a higher degree of polymerization is that less further curing is required in the process. On the other hand, a higher degree of polymerization may make it difficult to shape the object to be provided to the curing step. This will be discussed in more detail below. The degree of polymerization of the polymer in the composition provided to cure may preferably be at least 0.2, especially at least 0.3, especially at least 0.4, more especially at least 0.5. Preferably at most 0.7.
[0042] The composition provided to the curing step preferably has a water content of at least 2 wt.%, especially at least 4 wt.%. This is because water improves the effectiveness of RF heating. During the curing step, water will be produced by polymerization. The presence of water will make the HF heating more effective, thereby increasing the reaction rate of the polymerization. Therefore, a limited amount of water is usually sufficient. Therefore, the composition provided to the curing step preferably has a water content of at most 50 wt.%, especially at most 20 wt.%, especially at most 15 wt.%, more especially at most 11 wt.%. The water content can be determined by gravimetric analysis by comparing the weight of the composition with the weight of the same composition after all water has been removed by drying. As will be apparent to those skilled in the art, drying should be carried out under conditions that prevent polymerization from occurring.
[0043] As will be apparent to those skilled in the art, the polyester as described above may be the only polymer present in the composition. The presence of other polymers is not desired, necessary or required. Nevertheless, if desired, the composition may contain other polymers in an amount of up to 20 wt.%, preferably up to 15 wt.%, more preferably up to 10 wt.%, especially up to 5 wt.%, especially up to 2 wt.%.
[0044] The polymer used in the present invention is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms. The presence of other monomers is not desired, necessary or required. Nevertheless, if desired, the polymer may contain other monomers in an amount of up to 15 mole%, preferably up to 10 mole%, more particularly up to 5 mole%, especially up to 2 mole%.
[0045] filler
[0046] As mentioned above, the composition subjected to the curing step comprises a filler. Various types of fillers are conceivable. In general, particulate, fibrous and / or laminar fillers of natural or synthetic origin may be used. Combinations of various filler materials may be used. Based on the total weight of the composite object, fillers may be present in an amount of 10-95 wt.%, in particular 20-80 wt.%, more particularly 40-70 wt.%.
[0047] An example of a suitable filler is a particulate material. In the context of the present specification, a particulate material is a material having an aspect ratio in the range of 10:1 to 1:1, preferably in the range of 8:1 to 1:1, more preferably in the range of 6:1 to 11:1. As used herein, "aspect ratio" is defined as the ratio of the length measured along the longest axis of the particle to the maximum diameter of the particle measured along an axis perpendicular to the longest axis.
[0048] The granular material in the core layer has a maximum length of less than 20 mm, more preferably at most 15 mm, more preferably at most 10 mm, especially at most 5 mm, especially at most 2 mm, measured along the longest axis of the particles in the material. The minimum value of the average length of the particles may be 0.001 mm. In some embodiments, the average length of the particles is at least 0.05 mm, especially at least 0.1 mm, more especially at least 0.5 mm. In some embodiments, the average length of the particles is in the range of 0.5-5 mm, especially 0.5-2 mm.
[0049] Suitable granular materials may be in the form of powders, dusts, pulp, shredded fibers, flakes or chips, for example. Examples include wood chips, wood chips, sawdust, hemp chips, (dry) grass and pulp, for example (regenerated) pulp or other fiber pulp from sugar beet, fruit and vegetables, etc. Examples of plant-derived materials that can be used as granular materials are cotton, flax, hemp, grass, reeds, bamboo, coconut, Miscanthus, coffee grounds, seed husks (e.g. from rice, linen, kenaf, ramie, sisal, etc.) and materials derived from these plants. In general, plant materials that have been comminuted to a suitable particle size can be used and, if necessary, can also be dried to a suitable moisture content.
[0050] Granular material can comprise natural material, such as material from plant or animal.The example of plant-based material comprises cellulose-based material, such as fresh or used paper, fresh or used cardboard, wood or other plant materials of any form, and its combination.Cellulose-based material can be derived from the so-called virgin pulp obtained directly from wood pulping process.This paper pulp can come from any plant material, but mainly from wood.Wood pulp comes from softwood trees, such as spruce, pine, fir, larch and hemlock, and broad-leaved trees, such as eucalyptus, poplar, mountain poplar and birch.In addition or alternatively, cellulose-based material can comprise cellulose material from recycled paper, such as cellulose pulp obtained from recycled books, paper, newspaper and periodicals, egg boxes and other recycled paper or paperboard products.Also can use the combination of cellulose source.Other attractive cellulose-based material sources are waste paper fibers, i.e. paper fibers that are too short to be suitable for papermaking, and any (by mechanical and / or chemical means) regenerated materials (from any (composite) material, such as recycled furniture made of cellulose-based material). In particular, (composite) materials made with the polymers mentioned here as binders are an attractive source of cellulose-based materials. The use of these (recycled) materials is highly sustainable and cost-effective and can be widely used, for example, in furniture manufacturing.
[0051] Examples of animal-derived materials include feathers, down, hair and its derivatives, such as wool, and bone meal.
[0052] Other examples of suitable granular materials include ceramic materials, including oxides, such as aluminum oxide, beryllium oxide, cerium dioxide, zirconium oxide, silicon dioxide, titanium dioxide and mixtures and combinations thereof, and non-oxides, such as carbides, borides, nitrides, silicides and mixtures and combinations thereof, such as silicon carbide. For the purposes of this specification, glass is considered as a ceramic material. Glass can be used, for example, in the form of short fibers, glass beads (whether solid or hollow) and frosted glass particles. Suitable granular materials also include materials such as mica fillers, calcium carbonate and minerals (such as layered silicates). Clay, sand, talcum powder, gypsum, etc. can also be used.
[0053] Suitable granular materials also include polymer fillers, such as particles or short fibers of the following: polyethylene, polypropylene, polystyrene, polyester (such as polyethylene terephthalate), polyvinyl chloride, polyamide (for example, nylon 6, nylon 6.6, etc.), polyacrylamide and aramid polymers, such as aromatic polyamide. Suitable granular materials also include carbon fibers and carbon granular materials. Crushed cured polyester resins as used in the present invention can also be used as granular materials. Crushed cured polyester resins containing fillers can also be used. Adding carbon granular materials may be attractive for improving the RF heating characteristics of the object. Therefore, in one embodiment, a carbon granular material comprising at least 0.1wt.% is used as a filler, based on the total amount of filler used. Depending on the target composition, a combination of fillers can be used, and the combination of fillers can contain 0.1-10wt.%, especially 0.1-5w.%, for example 0.1-2wt.% of carbon granular materials based on the total amount of fillers. In some embodiments, a granular material containing one or more organic granular materials is used, the organic granular material being selected, for example, from pulp, wood flour, wood chips and recycled paper. In other embodiments, the granular material (also) contains one or more inorganic granular materials, the inorganic granular material being selected, for example, from (recycled) glass, stone, ceramic, minerals and metals.
[0054] Suitable fillers also include fibrous materials. In the context of this specification, fibrous materials refer to materials with an aspect ratio greater than 10:1.
[0055] In the context of this specification, the term "fiber" refers to monofilaments, multifilaments, threads, tapes, strips and other elongated objects having a regular or irregular cross-section and a length that is generally longer than its width and thickness.
[0056] Suitable fibrous materials can have a fiber length of at least 1 cm, preferably at least 3 cm, preferably at least 4 cm, measured along its longest axis. For example, the fibrous material can have a fiber length of 1-20 cm measured along its longest axis. Preferably, the fibrous material has a fiber length of 1-10 cm. Long (longer) fibers are preferred because long fibers provide strength to the composition.
[0057] The fibrous material may contain fibers with a diameter of 0.001 to 10 mm, preferably 0.01 to 1 mm, more preferably 10 to 500 μm. Thinner fibers are advantageous for many applications because the use of thinner fibers results in a smooth surface of the object. Panels. For example, in the manufacture of kitchen cabinets, a smooth surface is of course advantageous.
[0058] The fibers may, for example, have an aspect ratio in the range of 20: 1 to 200,000: 1, preferably in the range of 200: 1 to 20,000: 1, more preferably in the range of 250: 1 to 5000: 1. Using fibers with relatively large aspect ratios may result in a combination of high strength and a smooth surface.
[0059] The fibers useful as fillers in the present invention may be oriented in a random (eg, nonwoven sheet) or non-random manner. The fibrous material is preferably a nonwoven sheet.
[0060] In the context of this specification, "oriented in a non-random manner" refers to all structures in which fibers are oriented in a substantially regular manner relative to each other. Examples of layers containing fibers oriented in a non-random manner include woven layers, knitted layers, layers in which fibers are oriented in parallel, and any other layers in which fibers are connected to each other in a repeating pattern.
[0061] The orientation of fibers in a fibrous material can, for example, affect the strength of the final product. Thus, in some cases, it is preferred to orient the fibers in a manner that maximizes the strength of the article. In some embodiments, at least 50% of the fibers are oriented in parallel, preferably at least 60% of the fibers are oriented in parallel, and more preferably at least 70% of the fibers are oriented in parallel. In other cases, more anisotropic properties or bidirectional resistance may be desired.
[0062] Fibrous materials that can be used in the present invention The present invention can include plant-derived fibers, preferably cellulose fibers and / or lignocellulose fibers. Fibrous materials can also be essentially composed of plant-derived fibers. Examples of fibers based on plant-derived fibers include flax, hemp, kenaf, jute, ramie, sisal, coconut, bamboo and cotton. Fibrous materials can also include animal-derived fibers. Animal-derived fibers can be wool, hair, silk and fibers derived from feathers (e.g., chicken feathers). Other parts of viscera can also be used. Fibrous materials can include synthetic fibers. Examples of suitable synthetic fibers are fibers derived from viscose, glass, polyester, carbon, aromatic polyamide, nylon, acrylic resin, polyolefins, etc. Fibrous materials can also be a mixture of fibers from different sources, such as a mixture of plant-derived fibers and synthetic fibers.
[0063] The fibrous material used in the present invention preferably comprises plant-derived fibers, preferably cellulose fibers and / or lignocellulose fibers, and the fibrous material may particularly preferably consist essentially of plant-derived fibers. As mentioned above, examples of fibers based on plant-derived fibers include flax, hemp, kenaf, jute, ramie, sisal, coconut, bamboo and cotton, of which hemp may be particularly attractive.
[0064] In the context of this specification, the composition comprising filler and polymer also includes a composition in which the filler is provided in the form of a thin layer alternately stacked with a polymer layer. Suitable layered materials generally comprise at least 2 layers, especially at least 4 layers, at most 50 layers, especially at most 20 layers of fillers. The thickness of each filler layer is generally 0.1-10mm, especially 0.1-5mm, more especially 0.2-2mm. The total thickness of the object can be, for example, 0.5-200mm. The thickness of the polymer layer can be, for example, 10-4000 microns, especially 10-2000 microns, more especially 10 to 500 microns. Suitable fillers can be, for example, wood (also referred to as wood veneer). Plywood is a kind of example in the present embodiment. Other layered fillers such as paper or cardboard may also be applicable.
[0065] As will be appreciated by those skilled in the art, combinations of different types and materials may also be used as fillers.
[0066] In one embodiment, the composite object comprises a particulate filler and a polymer, in particular 10-95 wt.%, in particular 20-80 wt.%, more in particular 40-70 wt.% of the particulate filler, based on the total composite.
[0067] In another embodiment, the composite object comprises a fibrous filler and a polymer, in particular 10-95 wt.%, in particular 20-80 wt.%, more in particular 40-70 wt.% of the fibrous filler, based on the total composite.
[0068] In addition to the polymer and filler, the composition may contain other components, typically in minor amounts, such as colorants and stabilizers. Suitable other components will be apparent to those skilled in the art.
[0069] In one embodiment, the composition comprising a polymer and a filler further comprises an inorganic salt. It has been found that the presence of an inorganic salt increases the effectiveness of the heating method used herein.
[0070] If used, the amount of salt is generally at most 10 wt.%, based on the amount of polymer. The amount of inorganic salt may preferably be at most 5 wt.%, especially at most 2 wt.%, more especially at most 1 wt.%. The upper limit is determined by a variety of considerations. Too much salt can affect the properties of the composite object formed, including its recyclability, without bringing any benefit. If salt is added, the minimum value may be at least 0.01 wt.%, especially at least 0.05 wt.%, more especially at least 0.1 wt.%, based on the amount of polymer. If too little salt is added, the effect of increasing the effectiveness of the heating method will not be achieved.
[0071] The nature of the inorganic salt is not important for the present invention, and it is within the scope of those skilled in the art to select a suitable salt. Examples include inorganic salts of alkali metals (e.g., K, Na) or alkaline earth metals (e.g., Ca, Mg) and ammonium salts. As counterions, conventional counterions such as halides (e.g., chloride), nitrates, carbonates, and phosphates can be envisioned. Specific examples include NaCl, KCl, CaCl2, MgCl2, FeCl3, sodium phosphates, and ammonium salts (e.g., ammonium chloride, ammonium nitrate). Salts can be added to the composition in any suitable manner. For example, they can be blended with a polymer or incorporated into a filler, for example, by impregnation.
[0072] By adjusting the manner in which the salt is provided, the distribution of the salt in the composite object prior to curing can be affected. The salt may be provided uniformly in the composite object. However, it is attractive to provide the salt specifically near the outer surface of the composite object to be cured, where improved curing efficacy may be specifically desired. Thus, in one embodiment, the salt concentration in the outer 10 vol.% of the composite object is higher than the salt concentration in the core of the object, the core of the object being defined as the innermost 10 vol.% of the object.
[0073] One way to provide the salt near the surface of the composite object is to provide an impregnation material at or near the surface of the composite object before it is cured, for example in the form of an impregnation sheet. Other ways of providing a non-uniform distribution of salt in the composite object are also possible. For example, including providing the polymer and salt (e.g., 0.1-10 wt.%) in the outer layer of the composite object, and providing the polymer with less salt or no salt in the core of the composite object (e.g., 0-5 wt.% and less than in the outer layer).
[0074] In one embodiment, the composite object comprises at least two layers of the same or different composition.
[0075] In one embodiment, the composite object comprises at least two layers of different composition, wherein one layer comprises a fibrous filler and another layer comprises a particulate filler.
[0076] In one embodiment, the composite object is a panel comprising a core layer and at least one surface layer bonded to the core layer, wherein the core layer comprises a particulate material bonded to a polymer, and the surface layer comprises a fibrous material bonded to a polymer, wherein the ratio of the polymer content (in wt.%) of the core layer to the total polymer content (in wt.%) of the surface layer is in the range of 1 : 1.5 to 1 : 15. In this embodiment, a relatively light core layer comprising a particulate filler and having a relatively low polymer content is combined with at least one relatively dense surface layer having a higher polymer content and having good strength and surface properties due to the presence of the fibrous filler.
[0077] Preferably, the core layer is sandwiched between two surface layers.
[0078] In one embodiment, the thickness of the core layer is at least 1.5 mm, especially at least 2 mm, more especially at least 4 mm and / or at most 50 cm, especially at most 20 cm, more especially at most 10 cm, more especially at most 5 cm, even more especially at most 3 cm; and / or the thickness of the surface layer is at least 0.3 mm, especially at least 0.5 mm, more especially greater than 1 mm, even more especially at least 1.1 mm and / or at most 20 mm, more especially at most 10 mm, even more especially at most 5 mm, even more especially less than 5 mm.
[0079] Preferably, the ratio of the thickness of the core layer to the total thickness of the surface layers is in the range of 1:1 to 150:1, more preferably in the range of 1:1 to 50:1, more preferably 1:1 to 25:1, more preferably 2:1 to 25:1, more preferably 3:1 to 25:1, more preferably 5:1 to 20:1.
[0080] In one embodiment, the composite object is a panel, and the polymer content is in the range of 10-60 wt.%, preferably 15-50 wt.%, more preferably 15-40 wt.%, based on the total weight of the panel. The polymer content of the core layer is preferably in the range of 1-40 wt.%, preferably 2-30 wt.%, more preferably 5-20 wt.%, based on the total weight of the granular material and the polymer. The polymer content of the surface layer is preferably 10-90 wt.%, preferably 20-80 wt.%, more preferably 30-70 wt.%, even more preferably 40-60 wt.%, based on the total weight of the fibrous material and the polymer.
[0081] Preferably, the ratio of the polymer content (in wt.%) of the core layer to the total polymer content (in wt.%) of the surface layer may be in the range of 1:1.5 to 1:10, more particularly 1:2 to 1:8.
[0082] In the first step of the process of the present invention, a composition comprising a filler and a polyester polymer as described above is provided, wherein the degree of polymerization of the polyester is in the range of 0.1 to 0.8, the degree of polymerization being the ratio between the fraction of functional groups that have reacted and the maximum number of functional groups that can react.
[0083] There are a number of ways to provide this composition. In its simplest form, the filler is combined with the polymer in a liquid phase, optionally in the form of an aqueous solution. Depending on the nature of the filler, the combination may be carried out by mixing, dipping, pouring, rolling or any other means that ensures intimate contact between the filler and the polymer.
[0084] When the composite object consists of more than one layer, the compositions constituting the various layers may be prepared separately and then combined and then cured. It is also possible to superimpose the various layers.
[0085] When the polymer is provided in liquid form, it may have a relatively low degree of polymerization, for example between 0.1 and 0.5, and / or the liquid may contain a relatively large amount of water. When there is a relatively large amount of water, it is preferred that the composition comprising filler and polymer be subjected to a drying step before the pressurized curing step. The drying step may be performed by HF heating, but other methods may also be envisioned. The drying step will typically remove moisture, but may not necessarily achieve polymer curing (polymerization). The drying step may or may not be a HF heating step. Considering efficiency reasons, drying by HF heating may be preferred.
[0086] When the degree of polymerization of the polymer is relatively low, the pre-curing step may be carried out under pressure or without pressure. The pre-curing step may or may not be a HF heating step. For efficiency reasons, pre-curing by HF heating may be preferred.
[0087] In the method of the present invention, a shaping step may be performed. In the context of this specification, a shaping step is any step that pre-shapes the composite object. Pre-shaping includes flat plates, curved plates, and any other desired forms. Examples of suitable shaping steps include pressing between flat or curved surfaces, bending, and shaping using a mold.
[0088] The shaping step may be performed at various points in the process. For example, the shaping step may be combined with the curing step, for example by subjecting the composition to a curing step while it is present in a mould or provided on a surface. It is also possible to perform the shaping step at an earlier stage of the process, for example when the polymer is provided in liquid form, for example using a mould. Filament winding is an example of such a process. Other processes, such as free-forming or vacuum moulding, are also conceivable.
[0089] After curing, the degree of polymerization will generally be greater than 0.80, preferably greater than 0.90, more preferably at least 0.95, and most preferably at least 0.98. In addition, immediately after curing, the water content of the object is generally less than 10 wt.% (based on the total weight of the object), preferably less than 5 wt.%, in some embodiments less than 2 wt.% or less than 1 wt.%. Depending on the storage conditions, the water content of the object may increase after curing.
[0090] Preferably, the thickness of the object obtained by the method is in the range of 0.5 mm to 50 cm, preferably 3 mm to 20 cm, in a number of embodiments in the range of 3 mm to 10 cm or 3 mm to 5 cm. It has been found that HF heating is particularly advantageous for relatively thick materials, because the temperature is more uniform over the cross section of the object and the core of the object can be heated more quickly than in conventional oven heating. Thus, in some embodiments, the thickness of the object over the smallest cross section is at least 4 mm, in particular at least 6 mm. In some embodiments, the thickness may be at least 8 mm or at least 10 mm or at least 15 mm or even at least 20 mm.
[0091] In some embodiments, the flexural strength of an object made by the method of the present invention is greater than 20 MPa, for example as measured using ASTM D 7264. Depending on the intended use, the flexural strength may preferably be at least 40 MPa, especially at least 60 MPa. This range of values has been achieved using the present invention.
[0092] As is obvious to a person skilled in the art, different embodiments of the present invention can be combined unless mutually exclusive. Unless otherwise specified, all percentages used herein are percentages by weight.
[0093] When amounts, concentrations, sizes and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper values and limits, it should be understood that any range obtainable by combining any upper limit or preferred value with any lower limit or preferred value is also specifically disclosed, regardless of whether the resulting range is explicitly mentioned in the context. DETAILED DESCRIPTION
[0094] The present invention will be illustrated by the following examples, but the present invention is not limited thereto or thereby.
[0095] Example 1: Preparation of polyester polymer solution
[0096] Glycerol (1.0 kg, >99% purity) and citric acid (2.0 kg, >99% purity) are combined in a reaction vessel, stirred and heated. Boric acid (9 g, 0.5 m / m, >99% purity) is added. The mixture is heated to 135° C. in about 15 minutes and maintained at this temperature for 15 minutes. The mixture is then diluted with tap water, after which the water content of each batch is 20-50 wt.%. The mixture is cooled. The prepared composition is also referred to herein as a resin composition.
[0097] Example 2: Single-step method for manufacturing sandwich panels
[0098] Step 1: Prepare the Hemp Mat
[0099] From hemp roll (15×1m, thickness 10mm, 1100g / m 2, from Hempflax) cut two hemp mats (35×35 cm). The hemp mats are each impregnated with the resin composition obtained in Example 1. The diluted resin composition is evenly poured on one side of the hemp mat and evenly distributed on the hemp mat with the help of a rolling pin. The resin composition impregnation is carried out at room temperature. After these steps, the total amount of polymer impregnated into the mat is between 48-55 wt.%. The impregnated hemp mat is pre-cured (dried) in a 90° C. oven for 2 hours. It is then allowed to cool to room temperature.
[0100] Step 2: Prepare the core layer foundation
[0101] A granular material was prepared from 900 g of hemp chips. To this granular material was added 150 g of the resin composition of Example 1 and the resulting granular mixture was stirred. The polymer content of the granular mixture was 10 wt.%.
[0102] Step 3: Forming a layered structure
[0103] The first hemp mat is placed on a Teflon sheet, on which a square wooden mold (30×30 cm) is placed. The granular mixture is spread on the first hemp mat (inside the mold). The mold is equipped with a lid, and pressure is manually applied to the mold to pre-press the loose hemp particles. The mold is removed and a second hemp mat is placed on the granular mixture and the second Teflon sheet to prevent the structure from sticking to the press plate.
[0104] Step 4: Solidify the layered structure to obtain the panel
[0105] The loose sandwich structure obtained in step 3 was placed in a high-frequency press. The moisture content at this point was 6-7%. The loose sandwich structure was heated at 5×10 5 The pressing was carried out at a pressure of 1.50 Pa (5 bar) for a total of 3-5 minutes. The pressed panel was cooled under pressure for 2 minutes and then removed from the press. The temperature reached in the core was 130° C. The sandwich panel thus obtained had a smooth and uniform surface, as determined by touch and visual observation.
[0106] The panels were then subjected to a post-curing step by placing them in a conventional heating oven, preheated at 120° C. and cured at this temperature for 30 minutes, followed by 105 minutes at 160° C. Extending the exposure time in the high frequency press can eliminate the post-curing step.
[0107] The final panel density is 0.65g / cm 3 The thickness is 17mm and the bending strength is at the level of 30-40MPa.
[0108] Example 3: Making a 4-layer hemp panel
[0109] Four hemp mats (45 x 45 cm) were cut from hemp rolls (15 x 1 m, 10 mm thick, from Hempflax). The hemp mats were impregnated with the resin composition obtained in Example 1 in the manner described in Example 2. After these steps, the total amount of polymer impregnated into the mats was between 48 and 55 wt.%. The impregnated hemp mats were pre-cured (dried) in a conventional oven at 90° C. for 2 hours. They were then allowed to cool to room temperature.
[0110] Four layers of impregnated hemp mats were stacked on a high-frequency press plate, with the fibers in all mats oriented in the same direction. Teflon sheets were placed above and below the hemp structure to prevent it from sticking to the plate. A 1.5×10 5 Pa or 2.8×10 5 Pa (1.5 or 2.8 bar). HF heating was then performed at 6000 V for 3 to 4 minutes. The structure was then cooled for two minutes. The core temperature of the hemp board was 125°C.
[0111] The resulting object has a smooth and uniform surface and a density of 0.95-1 g / cm 3 The cross section of the panel is uniform and there is no delamination between the layers. The thickness of the panel is 8mm.
[0112] The panels were then subjected to a post-cure step by placing the panels in an oven preheated at 120° C. and curing at this temperature for 30 minutes, followed by curing at 160° C. for 105 minutes. A post-cure step was not believed to be necessary but was performed to ensure comparability with other samples.
[0113] The hemp panels from this example, as well as the hemp panels from Examples 4 to 6 below, all had flexural strengths in the range of 40-80 MPa.
[0114] Example 4: Fabrication of 4-layer hemp panels - 6300V energy input
[0115] Example 3 was repeated except that the power during the HF heating step was 6300 V instead of 6000 V. This resulted in a core temperature of the sample of 140° C. This example demonstrates that the core temperature can be modulated using energy input.
[0116] The resulting object has a smooth and uniform surface and a density of 0.95-1g / cm 3 The cross section of the panel is uniform and there is no delamination between the layers. The thickness of the panel is 8mm.
[0117] Example 5: Fabrication of 4-layer hemp panels - 6600V energy input
[0118] Example 3 was repeated except that the power during the HF heating step was 6600 V instead of 6000 V, and curing was carried out for 2 minutes instead of 3 minutes. The core temperature of the sample was 140°C, ie the same as in Example 4. This example shows that higher energy input can be used to reduce curing time.
[0119] The resulting object has a smooth and uniform surface and a density of 0.95-1g / cm 3 The cross section of the panel is uniform and there is no delamination between the layers. The thickness of the panel is 8mm.
[0120] Example 6: Making 8-layer hemp panels
[0121] The sample preparation steps were carried out as in Example 3. Instead of four layers, eight layers of impregnated hemp mat were stacked on top of each other. Pressing was carried out in two steps at a power level of 6300 V. The first processing step was carried out at 0.2×10 5 Pa (0.2 bar) for 1 minute to preheat the material and soften the polymer. This step helps to ensure more uniform compression during the second processing step. The core temperature after the first processing step was not measured to avoid cooling of the material. 5 Pa to 4×10 5 The second pressing was carried out at a pressure of 1.375 Pa (2-4 bar) for 3 minutes. The temperature of the core and surface of the structure was 145-150°C.
[0122] The object has a smooth and uniform surface and a density of 1 g / cm 3 The cross section of the panel is uniform and there is no delamination between the layers. The thickness of the panel is 16mm.
[0123] A post-cure step was performed as in Example 3. A post-cure step was not believed to be necessary but was performed to ensure comparability with other samples.
[0124] Example 7: Manufacturing of panels from recycled paperboard based porous material.
[0125] A 30 cm x 30 cm cellulose-based (recycled cardboard / recycled paper) insulation panel (8 x 50 x 120 cm) with a void fraction of 0.92 and a density of 90 g / L purchased from EverUse was used as the starting material. It was contacted with the resin composition of Example 1 to obtain a fully impregnated material. The final polymer content was 30 wt.%. The panel was heated at an estimated pressure of less than about 5 x 10 5 The curing was carried out in a press at 200 psi (5 bar) for a total of 2 minutes. After 2 minutes of cooling, the internal temperature was 160°C.
[0126] The resulting object was a panel with a thickness of 20 mm and a smooth and uniform surface.
[0127] Example 8: Manufacturing particleboard
[0128] A 30 cm x 30 cm particleboard panel was constructed as follows:
[0129] Two mixtures of the resin composition and birch wood chips were prepared. The mixtures differed in the particle size of the chips. The polymer content of the granulated mixture was 15 wt.%, based on the dry weight of polymer and filler. The granulated mixture was then dried at 120° C. for 1 hour.
[0130] A 30 cm x 30 cm wooden mould was filled in three layers in sequence: 50% of the fine chip mixture, all of the coarse chip mixture and the remaining 50% of the coarse chip mixture.
[0131] The panel was heated by HF at a frequency of 27.12 Hz at an estimated pressure below about 5 × 10 5 The curing was carried out in a press at 200 psi (5 bar) for a total of 5 minutes. After 2 minutes of cooling, the internal temperature was 160°C.
[0132] The resulting object was a panel with a thickness of 20 mm and a smooth and uniform surface.
[0133] Example 9: Manufacturing plywood
[0134] Plywood samples were made by stacking a wood facing layer with an intermediate layer of the resin composition of Example 1. The thickness of the facing layer was 1-1.5 mm. 5 layers were used. The total polymer content was about 15 wt.%. The total thickness of the stack was 7 mm.
[0135] The layers were stacked at a pressure of 5 × 10 5 The veneers were cured in a press at 400 °C (5 bar) for a total of 5 minutes. The adhesion properties of the veneers were found to be very good both in wet and dry conditions.
Claims
1. A method for manufacturing a composite object containing filler, comprising the following steps: - providing a composition comprising a filler and a polymer, wherein the polymer is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms, the degree of polymerization of the polyester being in the range of 0.1 to 0.8, the degree of polymerization being the ratio between the fraction of functional groups that have reacted and the maximum number of functional groups that can react, and - subjecting the composition to a curing step, wherein the composition is cured at a temperature of at most 1×10 6 High frequency heating is performed at a pressure of 100 Pa (10 bar) for a period of 10 seconds to 30 minutes, resulting in the formation of a composite object, wherein the high frequency heating is performed by subjecting the composition to an alternating electromagnetic field with a frequency in the range of 3 to 100 MHz.
2. The method according to claim 1, wherein high frequency heating is performed by subjecting the composition to an alternating electromagnetic field having a frequency in the range of 10 to 50 MHz, more particularly 13.56 MHz, 27.12 MHz or 40.68 MHz, even more particularly 27.12 MHz.
3. The method according to any one of the preceding claims, wherein high-frequency heating is performed for a period of 10 seconds to 20 minutes, in particular 20 seconds to 10 minutes, more particularly 20 seconds to 5 minutes or even 20 seconds to 3 minutes.
4. A method according to any one of the preceding claims, wherein the curing step is performed at a temperature of at most 8×10 5 Pa (8 bar), especially up to 6×10 5 Pa (6 bar) or up to 4×10 5 Pa (4 bar), in some embodiments up to 3×10 5 Pa (3 bar), and at least 1.1×10 5 Pa (1.1 bar), especially at least 1.5×10 5 Pa (1.5 bar) pressure.
5. The method according to any one of the preceding claims, wherein the water content of the composition subjected to the high-frequency curing step is at least 2 wt.%, especially at least 4 wt.% and at most 50 wt.%, especially at most 20 wt.%, more especially at most 15 wt.%, even more especially at most 11 wt.%.
6. The method according to any one of the preceding claims, wherein the polymer is a polyester derived from an aliphatic polyol having 2 to 15 carbon atoms and an aliphatic polycarboxylic acid having 3 to 15 carbon atoms, wherein the aliphatic polyol comprises at least 30 wt.%, especially at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.% of a polyol having at least 3 hydroxyl groups, the aliphatic polyol having at least 3 hydroxyl groups being preferably glycerol, and the aliphatic polycarboxylic acid comprises at least 30 wt.%, preferably at least 50 wt.%, more preferably at least 70 wt.%, even more preferably at least 90 wt.%, most preferably 95 wt.% of a tricarboxylic acid, based on the total amount of acid, the tricarboxylic acid being preferably citric acid.
7. A process according to any one of the preceding claims, wherein the polymer having a degree of polymerization in the range of 0.1 to 0.8 is obtained by subjecting the mixture of polyol and polycarboxylic acid in liquid phase to a reaction step at a temperature in the range of 20°C to 250°C, such as 40°C to 200°C, such as 60°C to 200°C or 90°C to 200°C.
8. The method according to any one of the preceding claims, wherein the amount of filler is 10-95 wt.%, especially 20-80 wt.%, more especially 40-70 wt.%, based on the total weight of the composite object.
9. The method according to any of the preceding claims, wherein the composite object comprises at least two layers of the same or different composition.
10. A method according to any one of the preceding claims, wherein the composition comprising filler and polyester is provided by combining the filler with the polymer while the polymer is in liquid phase, optionally in the form of an aqueous solution, followed, if necessary, by one or more of a drying step, a shaping step or a pre-curing step.
11. A method according to any one of the preceding claims, wherein the method comprises a shaping step.
12. A method according to any of the preceding claims, wherein after curing, the degree of polymerization of the polymer is greater than 0.80, preferably greater than 0.90, more preferably at least 0.95, and most preferably at least 0.98, and the water content of the filler-containing composite object is less than 10 wt.% (based on the total weight of the object), preferably less than 5 wt.%, in some embodiments less than 2 wt.% or less than 1 wt.%.
13. A method according to any of the preceding claims, wherein the composite material after the curing step has a thickness of at least 4 mm, in particular at least 6 mm, in the smallest cross-section of the object, and in some embodiments, the thickness may be at least 8 mm or at least 10 mm or at least 15 mm or even at least 20 mm.
14. The method according to any one of the preceding claims, wherein the composition comprising filler and polymer further comprises an inorganic salt.
Citation Information
Patent Citations
Composite material comprising bio-filler and specific polymer
WO2012140237A1
Composite material comprising synthetic filler and specific polymer
WO2012140239A1